A deprotonation pathway to reactive [B]CH2 boraalkenes. Issue 19 (6th May 2022) - Škoch, Karel; Chen, Chaohuang; Daniliuc, Constantin G.; Kehr, Gerald; Erker, Gerhard
Abstract : The BH compounds IMes(Ar F )BH(NTf2 ) (Ar F : C6 F5 or FpXyl) were converted to the IMes(Ar F )BCH2 boraalkenes in a three step reaction sequence of B-methylation with methyllithium, hydride abstraction and deprotonation. Abstract : The BH compounds IMes(Ar F )BH(NTf2 ) (Ar F : C6 F5 or FpXyl) were converted to the IMes(Ar F )BCH2 boraalkenes in a three step reaction sequence of B-methylation with methyllithium, hydride abstraction and deprotonation. The BCH2 boraalkenes reacted with elemental sulfur to give a thiaborirane product. They underwent [2+2] cycloaddition reactions with carbon dioxide or sulfur dioxide to give four-membered boron containing heterocycles. The boraalkenes added strongly Lewis acidic boranes at their CH2 carbon atoms. The corresponding HB(C6 F5 )2 /boraalkene adduct reduced carbon monoxide to a –OCH(C6 F5 )– moiety inside a five-membered heterocycle at the B–CH2 –B template. The boraalkenes reacted with the [(Me2 S)AuCl] reagent to form the corresponding (boraalkene)AuCl complexes.